Factors involved in specific transcription by mammalian RNA polymerase II: role of transcription factors IIA, IID, and IIB during formation of a transcription-competent complex. - Maldonado, E (1990)
Human transcription factor TFIID, the TATA-binding protein, was partially purified to a form capable of associating stably with the TATA motif of the adenovirus major late promoter. Binding of the human and yeast TFIID to the TATA motif was stimulated by TFIIA. TFIIA is an integral part of a complex capable of binding other transcription factors. A complex formed with human TFIID and TFIIA (DA complex) was specifically recognized by TFIIB. We found that TFIIB activity was contained in a single polypeptide of 32 kDa and that this polypeptide participated in transcription and was capable of binding to the DA complex to form the DAB complex. Formation of the DAB complex required TFIIA, TFIID, and sequences downstream of the transcriptional start site; however, the DA complex could be formed on an oligonucleotide containing only the adenovirus major late promoter TATA motif. Using anti-TFIIB antibodies and reagents that affect the stability of a transcription-competent complex, we found that yeast and human TFIID yielded DAB complexes with different stabilities.